Effects of irradiation energy and nanoparticle concentrations on the structure and morphology of laser sintered magnesia with alumina and iron oxide nanoparticles. Issue 6 (15th April 2020) - García-Quiñonez, L.V.; Mendivil-Palma, M.I.; Roy, T.K. Das; Castillo-Rodríguez, G.A.; Gómez-Rodríguez, C.; Fernández-González, D.; Shaji, S.
Abstract: The laser sintering mechanism of composites based on magnesia and oxide nanoparticles was studied in terms of nanoparticle concentration and laser energy fluence. Iron oxide and aluminum oxide nanoparticles were mechanically mixed with magnesia (MgO) powder (5, 7 and 10 wt%) and the compacted pellets were irradiated with the fundamental output (1064 nm) of a pulsed Nd:YAG laser at 2.5 and 3.0 J/cm 2 . Crystal structure, elemental composition and morphology were characterized by X-ray diffraction, X-ray photoelectron spectroscopy and scanning electron microscopy. X-ray diffraction results confirmed the crystalline phases and spinel formation by addition of oxide nanoparticles and laser sintering. X-ray photoelectron spectroscopy analysis confirmed their surface composition and chemical states of the corresponding elements. Morphological changes were observed due to the laser fluence and the oxide nanoparticle concentrations. Results show that a coarsening mechanism was predominant with a high energy fluence and concentration of oxide nanoparticles.